Cover. Issue 11 (6th November 2019) - Zhang, Yifan; Tian, Jiehua; Wei, Donghao; Di, Ping; Lin, Ye
Abstract : The cover image is based on the Original Article Quantitative Clinical Adjustment Analysis of Posterior Single Implant Crown in A Chairside Digital Workflow: A Randomized Controlled Trial by Ye Lin et al., https://doi.org/10.1111/clr.13519 .